Analisis Faktor Yang Berhubungan Dengan Kelengkapan Imunisasi Pada Anak Usia 2-5 Tahun Di Desa Kelampaian Ilir Kecamatan Astambul Tahun 2024 - Rafi'ah Rafi'ah (HB PRESS, 2024)
The coverage of complete basic immunization in the working area of UPTD Puskesmas Astambul, Banjar Regency, has shown a declining trend. In 2022, only 64.16% of 572 targeted children were immunized, dropping to 61.8% of 565 targets in 2023. Kelampaian Ilir Village had the lowest coverage, with only 46.9% (15 of 34 toddlers) receiving complete immunization. To analyze factors associated with immunization completeness among children aged 2–5 years in Kelampaian Ilir Village, Astambul Subdistrict, in 2024. This correlational analytic study used a cross-sectional design. The population was all toddlers aged 2–5 years targeted for complete immunization, totaling 82 individuals, using total sampling. The study was conducted from August to December 2024. Independent variables included maternal knowledge, employment status, and family support. The dependent variable was immunization completeness. Data were collected via questionnaires and analyzed using the Chi-Square test. Maternal knowledge was significantly associated with immunization completeness (p = 0.032); mothers with good knowledge had more children with complete immunization. Family support was not significantly associated (p = 0.064); 56.9% of supported families still had incomplete immunization. Maternal employment status also showed no significant association (p = 0.186). Maternal knowledge is significantly associated with immunization completeness, while family support and maternal employment status are not significantly related.